THE MORAL THOUGHT OF KH. AHMAD DAHLAN AND ITS RELEVANCE TO CONTEMPORARY ISLAMIC EDUCATION - Mubarok; M. Mubin; Moh Sholeh; Benny Ptasetiya (Education Research Center, 2026)
Contemporary Islamic education faces increasingly complex challenges, particularly those related to moral crises, character degradation, individualism, and the influence of digital technological developments on students’ social behavior. These phenomena indicate that education has not yet been fully successful in shaping individuals who possess moral integrity, spirituality, and comprehensive social responsibility. Based on these issues, this study aims to analyze the moral thought of KH. Ahmad Dahlan and examine its relevance to contemporary Islamic education. This research employs a qualitative approach based on library research using historical and contextual hermeneutic approaches. Primary data were obtained from the works, thoughts, and documents related to KH. Ahmad Dahlan, while secondary data were derived from scientific journals, academic books, and various studies relevant to Islamic education and character education. The data analysis technique was conducted through content analysis and contextual interpretation to understand the construction of KH. Ahmad Dahlan’s moral thought within the context of modern education. The findings reveal that KH. Ahmad Dahlan’s concept of moral education is built upon the principles of tawhid (Islamic monotheism), the integration of knowledge and action, exemplary conduct, and social concern. Education is not only directed toward intellectual achievement but also toward the formation of humanistic, moderate, and transformative character. This study confirms that KH. Ahmad Dahlan’s moral thought holds strong relevance as a paradigm of Islamic character education in addressing the challenges of the digital era, multiculturalism, and the moral crisis of modern society.